Content validity of construction quality management of industrialised building system (IBS) related project in Malaysia - Zawawi M.H.; Azman N.S.; Ramli M.Z.; Roslin N.T. (American Institute of Physics Inc., 2023)
Construction industry is one of the key players in developing a country. However, the industry is often plagued with the same problem which is maintaining the quality. Industrialized Building System (IBS) has been identified as a potential method to improve overall construction performance in term of quality, cost effectiveness, safety and health, waste reduction and productivity. This paper is to focus on highlighted the success factors and validate the content of an instrument for factors that affect the quality of construction projects in Malaysia. A panel of 37 experts was used to validate the instrument through Content Validity Index (CVI). It was found that the highest kappa coefficient value is 1.000 for item; 'Consideration for the selection and position of special equipment for the transportation and handling of IBS components', 'Site layout has storage areas for materials', and 'Comprehensible structure of process planning and control'. 2020 Author(s).